Pengaruh Etika Profesi, Pengalaman Kerja, Independensi dan Keahlian Audit Terhadap Ketepatan Pemberian Opini Auditor (Studi Empiris Pada Kantor Akuntan Publik di Jawa Tengah) - Nugraheni, Fadilla Alfi, Drs. Wahyono, M.A., Akt (2016)
This research is intended to analyze the effect of the professional ethics, work experience, independence, and auditing expertise on the accuracy in giving opinion by the auditor. The population in this research are all auditors working in the public accounting firm in Central Java. The sampling method was done by using convenience sampling. The number of samples collected as many as 47 auditors. The data analyze technique in this research using multiple regression analysis. The results of this research showed that the the professional ethics, work experience, independence, and auditing expertise have significantly effect on the accuracy in giving opinion by the auditor.